Ionic Composition of Rainwater at Selected Sites of Kuantan, Pahang, Malaysia: A Preliminary Study - Tay, Joo Hui; Syakhsiah, Jaafar; Norhayati, Mohd Tahir (Elsevier, 2014)
A short-term investigation on the chemical composition of rainwater was carried out at five selected sampling stations in Kuantan district, Pahang, Malaysia. Sampling of rainwater was conducted by event basis between September and November 2011. Rainwater samples were collected using polyethylene containers and the parameters measured were cations (sodium, potassium, ammonium, calcium and magnesium) and anions (chlorides, nitrates and sulphates). The average pH value for rainwater samples was 6.0 ± 0.57 in which most of the sampling sites exhibited pH values >5.6. Calcium and sulphate were the most abundant cation and anion, respectively, whilst the concentrations of other major ions varied according to sampling location.